The maintenance of white heteronormativity in porn films that use Australia as an exotic location. Issue 1 (2nd January 2017) - Gregory, Tim
ABSTRACT: Exotic locations are used in pornography to generate distance between the audience and the explicit content. The 'pornoexotic' maintains white heteronormativity through presenting the exotic as a zone of anomie, where taboo desires can be satisfied. This article examines Australia as a unique pornoexotic location through four pornographic feature films. The Australian pornoexotic functions to geographically and symbolically distance the viewer while simultaneously presenting bodies and desires that do not deviate from white, heteroporn standards. It achieves this through a focus on the landscape, through the character arc of a coerced outsider and through the symbolic investment in but absence of Aboriginal people. The invisibility of Aboriginal people in porn can be contextualized through the ongoing neocolonial measures restricting Aboriginal people's access to pornography. This article examines one of the most recent neocolonial measures regulating Aboriginal sexuality – the Northern Territory Emergency Response, which banned pornography in a number of Aboriginal communities.